TEXT BOOK OF BOTANY FOR DEGREE STUDENTS: VOLUME 1 VOLUME 2 - HAIT, GOPINATH; BHATTACHARYA, KASHINATH; GHOSH, ASHIM KUMAR (London New Central Book Agency, 2007)
About the Book: A Textbook Of Botany (Vol. I) The book logically explores the topics in a series of concise, yet well documented and profusely illustrated chapters. The text is divided into seven broad chapters: Introduction, Bacteria and Viruses, Algae, Fungi and Lichens, Plant Pathology, Bryophytes, and Pteridophytes; and every attempt has been made to bring together almost all the branches of A Cryptogamic Botany with both their fundamental and applied aspects
Keywords: Botany; Plant